2021
DOI: 10.1101/2021.03.05.433425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semaphorin3F Drives Dendritic Spine Pruning through Rho-GTPase Signaling

Abstract: Dendritic spines of cortical pyramidal neurons are initially overproduced then remodeled substantially in the adolescent brain to achieve appropriate excitatory balance in mature circuits. Here we investigated the molecular mechanism of developmental spine pruning by Semaphorin 3F (Sema3F) and its holoreceptor complex, which consists of immunoglobulin-class adhesion molecule NrCAM, Neuropilin-2 (Npn2), and PlexinA3 (PlexA3) signaling subunits. Structure-function studies of the NrCAM-Npn2 interface showed that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…By contrast, those spines in which NRP2 clusters with NrCAM are pruned by binding with SEMA3F [ 67 , 68 ]. As shown with structural and functional experiments, SEMA3F induces surface clustering of NrCAM/NRP2/PLXNA3, activating Rac1 and RhoA pathways [ 70 ]. Specifically, upon binding, PLXNA3 intracellular domain inactivates Rap1, allowing activation of the RhoA-ROCK1/2-Myosin II pathway for actin remodeling.…”
Section: Synaptic Plasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, those spines in which NRP2 clusters with NrCAM are pruned by binding with SEMA3F [ 67 , 68 ]. As shown with structural and functional experiments, SEMA3F induces surface clustering of NrCAM/NRP2/PLXNA3, activating Rac1 and RhoA pathways [ 70 ]. Specifically, upon binding, PLXNA3 intracellular domain inactivates Rap1, allowing activation of the RhoA-ROCK1/2-Myosin II pathway for actin remodeling.…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…Specifically, upon binding, PLXNA3 intracellular domain inactivates Rap1, allowing activation of the RhoA-ROCK1/2-Myosin II pathway for actin remodeling. Concomitantly, Tiam1 is recruited, activating the Rac1-PAK-LIMK-Cofilin pathway to provide for spine destabilization and finally cytoskeletal disassembly [ 70 ]. Although the regulatory mechanism remains to be fully explained, it is interesting to notice that both SEMA3B and SEMA3F release is activity-dependent [ 69 , 70 ].…”
Section: Synaptic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…The L1 family cell adhesion molecules Neuron-glia related protein (NrCAM) and Close Homolog of L1 (CHL1) mediate selective pruning of dendritic spine subpopulations in the mouse neocortex in response to class 3 secreted Semaphorins (Sema3s) through an activity dependent mechanism (Tran et al, 2009;Mohan et al, 2019a;Mohan et al, 2019b). Heterotrimeric receptors comprising L1-CAMs, Neuropilins (Npn1-2), and PlexinAs (PlexA1-4) transduce Sema3 signals to achieve selective spine pruning (Duncan et al, 2021a;Duncan et al, 2021b). All L1-CAMs share a conserved cytoplasmic domain containing the motif FIGQY (FIGAY in CHL1) that binds the actin-spectrin adaptor protein Ankyrin when the tyrosine (Y) residue is not phosphorylated (Bennett and Healy, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies with L1-CAM-deficient mouse models have revealed novel roles for NrCAM and CHL1 in constraining the density of dendritic spines and excitatory synapses on apical dendrites of cortical pyramidal neurons in the PFC (32-35). Distinct spine subpopulations are pruned in response to secreted Semaphorin-3 ligands Sema3F and Sema3B through receptor complexes comprising NrCAM/Neuropilin2/PlexinA3 and CHL1/Neuropilin2/PlexinA4, respectively.…”
Section: Introductionmentioning
confidence: 99%